PASSIONFLOWER EXTRACT AND ITS USAGE IN MEDICINE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
Herbal medicines include a range of pharmacologically active compounds: in some cases, it is not well understood which ingredients are important for a therapeutic effect. The supporters of herbal medicine believe that isolated ingredients in the majority of cases have weaker clinical effects than whole plant extract, a claim that would obviously require proof in each case. Generalizations about the efficacy of herbal medicines are clearly not possible. Each one needs systematic research including a variety of animal studies and also randomized clinical trials. In this article we focus on Passiflora incarnat a and Salvia officinalis.